HAKIM MAHKAMAH KONSTITUSI REPUBLIK INDONESIA SEBAGAI PENGAWAL PANCASILA DALAM SISTEM HUKUM NASIONAL - Ramdhan, Mochamad Isnaeni (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2009)
The authority of the Constitutional Court of the Republic of Indonesia has been regulated by Article 24C The Amandment of1945’s Constitution, among other to judicial review certain lawsagainst the constitution. Such review includes the materiel andformiel review, so the the Constitutional Court can protect thesubtantial norm which has been given by the constitution asthe guidance for further regulation by the act. The review mechanism based upon the higher norm eliminates the lower norm,so in the future, the Constitutional Court should review the article of the constitution to Preambule of the 1945 Constitutionin which the Pancasila values have been formulated as thesource of the regulation in indonesia.